Malaysians’ popular online shopping websites during movement control order (MCO) - Isa, Khairunesa; Shah, J. M.; Palpanadan, Sarala @ Thulasi; Isa, F. (WARSE, 2020)
Movement Control Order (MCO) has been announced since the pandemic of corona virus spread cases increased dramatically. The key point emphasized in the implementation of MCO is a social distancing where is only one person is allowed to go out to seek daily necessities during daytime. Moreover, only selected essential business is allowed to operate with limited hour from 8 am to 8 pm only. Due to this order, the e-commerce has become an option to most consumers to fulfill their wants and needs. This paper presents the descriptive data that shows the shopping website that has been mostly visited by the consumers during the MCO phase one and phase two and the influencing factors of selected web sites to purchase during MCO. A survey was conducted throughout the country including Sabah and Sarawak using an open-ended questionnaire that was distributed online. A quantitative method with a descriptive research design was adopted to explore the data obtained in relation to the objective of the research. A total number of 280 adults from 14 states provided valid responses to the online questionnaire. The findings show that the top three shopping website that has been visited by the consumers were the Shopee, Lazada and Food Panda that sell general daily necessities needed by the consumers. The findings also showed that the elements of comfortable website referring to the attractive design, friendly user, having a selection of native language, amount of uploaded information and updating of the product details were the factors that contribute towards the attractions of consumers to be involved in online purchasing.